2015
DOI: 10.1007/s00289-015-1403-7
|View full text |Cite
|
Sign up to set email alerts
|

A new route to polymeric materials derived from chitosan and natural rubber

Abstract: In this work, the synthesis and characterization of a new polymer, natural rubber-g-chitosan, from biopolymers available in nature is reported. In this process, soft and amorphous natural rubber (NR) is converted into a relatively more dimensionally stable new polymer (glass transition temperature changes from -68 to ?94.5°C), with versatile solubility in a variety of common organic solvents. For this purpose, mild epoxidation of NR is carried out to provide a reactive handle for the grafting of chitosan. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As shown in Figure , the C–H bending vibration peak of methyl or the amide III band of CS near 1368 cm –1 changes from a single peak to a double peak in the supramolecular polymer spectrum with the introduction of CS and PVA, indicating that the characteristic peaks of both the methyl absorption peak related to ENR and the amide III band related to CS are presented in the composite. Moreover, the double peak is most obvious in the spectra of supramolecular polymers with 10 wt % CS and 30 wt % PVA, and the continued increase in the CS and PVA contents changes the double peak back to a single peak.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure , the C–H bending vibration peak of methyl or the amide III band of CS near 1368 cm –1 changes from a single peak to a double peak in the supramolecular polymer spectrum with the introduction of CS and PVA, indicating that the characteristic peaks of both the methyl absorption peak related to ENR and the amide III band related to CS are presented in the composite. Moreover, the double peak is most obvious in the spectra of supramolecular polymers with 10 wt % CS and 30 wt % PVA, and the continued increase in the CS and PVA contents changes the double peak back to a single peak.…”
Section: Resultsmentioning
confidence: 95%
“…3. The composites had one-step degradation process which occurred within 385 ᵒC [14]. It showed that CS slightly effected on thermal stability of the composites when compare to NR with no filler.…”
Section: Resultsmentioning
confidence: 98%
“…3,4 In certain composite applications, bio-based resins have been shown to be competitive to synthetic polymers. 5,6…”
Section: Introductionmentioning
confidence: 99%